2012
DOI: 10.1073/pnas.1200206109
|View full text |Cite
|
Sign up to set email alerts
|

Cryo-EM structure of a transcribing cypovirus

Abstract: Double-stranded RNA viruses in the family Reoviridae are capable of transcribing and capping nascent mRNA within an icosahedral viral capsid that remains intact throughout repeated transcription cycles. However, how the highly coordinated mRNA transcription and capping process is facilitated by viral capsid proteins is still unknown. Cypovirus provides a good model system for studying the mRNA transcription and capping mechanism of viruses in the family Reoviridae … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
58
1

Year Published

2015
2015
2022
2022

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 53 publications
(61 citation statements)
references
References 44 publications
2
58
1
Order By: Relevance
“…3f, Extended Data Figs 9, 10f-k). Consistent with previous icosahedral reconstructions, our asymmetric reconstructions show that the capsid shell of t-CPV expands outwards from q-CPV, with the maximal (~10 Å) expansion occurring at the vertex region 20,21 , to which Module A of the bracelet domain is attached (Fig. 4e,f).…”
supporting
confidence: 90%
“…3f, Extended Data Figs 9, 10f-k). Consistent with previous icosahedral reconstructions, our asymmetric reconstructions show that the capsid shell of t-CPV expands outwards from q-CPV, with the maximal (~10 Å) expansion occurring at the vertex region 20,21 , to which Module A of the bracelet domain is attached (Fig. 4e,f).…”
supporting
confidence: 90%
“…In comparing our results to the high-resolution structures of the transcriptionally-active subviral particle of cypo virus, a member of the same viral family as RV (i.e., Reoviridae), we found an essential commonality-a series of conformational changes must occur in the viral capsid during mRNA synthesis, capping, and egress [14]. It remains unknown whether this process is being driven by the structural mobility of the internal RNA genome or by fluid protein rearrangements in response to the changing RNA landscape during transcription.…”
Section: D Reconstructions Reveal a Continuum Of Features That Reprementioning
confidence: 79%
“…Analysis of the three-dimensional structure of BmCPV by cryoelectron microscopy (cryo-EM) revealed that mRNA capping occurred in the enzymic domains of the pentameric turret whose five unique channels guide nascent mRNA sequentially to GTase, N structural comparison via cryo-EM of transcribing and non-transcribing BmCPV showed that transfer of a GMP moiety occurred to the 59 end of the diphosphate-ended RNA after its binding to Lys234 of the GTase pocket via a phosphoamide linkage (Yang et al, 2012) and then the RNA capping reaction occurred in the active sites of different turret protein monomers (Zhu et al, 2014) In the case of viruses lacking a pentameric turret, core protein VP3 (in the case of rotavirus) or VP4 [in the case of bluetongue virus (BTV)] provides both GTase and MTase activity for capping the 59 end of viral RNA (Trask et al, 2012). In many viruses, GTase activity has been reported to be associated with RTPase activity, such as mammalian reoviral m2 (Kim et al, 2004;Noble & Nibert, 1997b) and l1 proteins Noble & Nibert, 1997a), avian reoviral mA protein (Su et al, 2007), rotaviral NSP2 protein (Vasquez-Del Carpio et al, 2006, dengue viral NS3 protein (Bartelma & Padmanabhan, 2002), aquareoviral VP5 protein (Attoui et al, 2002) and alfavirus NSP2 protein (Vesiljeva et al, 2000), which not only has RTPase activity but also GTase activity.…”
Section: Cytoplasmic Polyhedrosis Virus Belongs To the Genusmentioning
confidence: 99%